DEVELOPMENT OF GEOMETRY TEACHING MODULES BASED ON MATHEMATICAL LITERACY USING TESTS IN PARTIAL CREDIT MODEL SCALE FOR JUNIOR HIGH SCHOOL IN EAST KALIMANTAN - Sugeng, Sugeng; Kukuh , Kukuh; Rahmayani, Hesti (Educational Studies: Conference Series, 2023)
The research aims to produce products in the form of Geometry teaching modules based on Mathematical Literacy with Geometry problems with a Partial Credit Model (PCM) scale at the junior high school level. The research subjects of junior high school students in the East Kalimantan region are represented by several district/city public junior high schools as the implementation of development and dissemination trials. The research and development process follows the flow of the 4-D model ((Define, Design, Develop, Disseminate) by involving several expert validators (material and language), as well as validation from several mathematics teachers and some students. The results of this development research show that the product in the form of a Geometry Teaching Module meets the criteria of feasibility, validity, practicality, and effectiveness. For further study, it is better to use geometry material and different school levels and development models, still using Partial Credit Model scale geometry questions to compare the quality of module products.